2004
DOI: 10.1016/j.joca.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cells from pannus-like tissue over articular cartilage of advanced osteoarthritis

Abstract: Our results showed that OA pannus cells shared the property of mesenchymal cells and chondrocytes; however, their origin seemed different from chondrocytes or synoviocytes. The spontaneous expression of MMPs suggests that they are involved in the articular degradation in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 27 publications
3
53
0
Order By: Relevance
“…Formation of pannus tissue containing lymphocytes, macrophages, neutrophils, and fibroblasts and the growth of this tissue, which can invade and destroy the cartilage, could be stimulated in part by release of cytokines and chemokines by the chondrocytes in response to the initial matrix damage. Synovial inflammation and pannus formation have also been noted in patients with advanced OA (35,36), although usually not to the extent seen in RA. This is most likely due to a greater influx of cells into the joint driven by the early inflammatory activity in the RA synovium, while local generation of chemokines in OA cartilage would attract fewer cells to the joint due to the avascular nature of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of pannus tissue containing lymphocytes, macrophages, neutrophils, and fibroblasts and the growth of this tissue, which can invade and destroy the cartilage, could be stimulated in part by release of cytokines and chemokines by the chondrocytes in response to the initial matrix damage. Synovial inflammation and pannus formation have also been noted in patients with advanced OA (35,36), although usually not to the extent seen in RA. This is most likely due to a greater influx of cells into the joint driven by the early inflammatory activity in the RA synovium, while local generation of chemokines in OA cartilage would attract fewer cells to the joint due to the avascular nature of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al studied the characteristics of cells isolated from pannus-like soft tissue on osteoarthritic cartilage. He described that the osteoarthritis pannus-like cells shared the property of mesenchymal cells, chondrocytes, and the tissue involved in cartilage degeneration in osteoarthritis [20]. In 1996, the recruitment of mesenchymal cells from the synovial membrane into the partialthickness cartilage defect was reported by Hunziker E et al They described how their histological findings revealed a continuous layer of mesenchymal cells extending from the synovial membrane across the superficial tangential zone of normal articular cartilage into the defect, indicating that the cells that were recruited for the repair process were synovial in origin Study 1 and Study 2 shows the total mean score a At 2 and 4 weeks after surgery, Pineda's score showed no significant difference between cartilage defect with intact synovium group and cartilage defect without synovium group.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that foci and plaque formation of the pannus-like tissue over cartilage surface were found in an osteoarthritic knee, and the pannus-like tissue was found at the margins of articular surface or in more central areas [20]. However, whether the invading synovium forms cartilage-like tissue or degenerate cartilage has remained unclear [1,2,4,16].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-1 and MMP-13 preferentially degrade type II collagen and may be most important in OA pathogenesis (Amalinei et al, 2007;Burrage et al, 2006). MMP-3 secreted by osteoarthritis synovial tissue was involved in direct extra-cellular matrix (ECM) breakdown (Yuan et al, 2004). ADAMTS-5 is the primary aggrecanase responsible for aggrecan degradation and ADAMTS-5 knockout mouse showed significantly reduced cartilage destruction (Glasson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%